PENERAPAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) PADA MESIN ADHESIVE DI PT. ASIA CHEMICAL INDUSTRY - Anggi Hermawan; Doto Doto; Rahmat Akmal (LPPM Universitas Bina Bangsa, 2022)
PT. Asia Chemical Industry (ACI) is a company engaged in the field of Chemical Adhesives. It is management policy to produce high quality and consistent Adhesives. In accordance with the standards determined by consumers and always maintain customer satisfaction with quality standards through specification information that is included in every shipment, sale, in addition to competitive price factors from similar companies. The adhesive in the process often experiences production delays caused by the adhesive machine (waterbase latex mixer) caused by non-routine maintenance of machine components so that the machine production is damaged which causes breakdown, resulting in downtime. As a result, the performance time is reduced, the production of the resulting product quality results in losses. Therefore, an effective step in the analysis of total predictive maintenance to measure the performance level of the adhesive machine can use the OEE method to determine the performance level of the adhesive machine that has decreased, and the FMEA method to analyze the proposed improvement. From the research conducted, the results of the OEE calculation on the adhesive machine during the period January - December 2021 obtained OEE values ​​ranging from 69.02% to 81.40%. This condition indicates that the adhesive machine's ability to achieve the target has not yet reached the ideal condition, which is below 85%. . The factor that gives the biggest contribution to the adhesive machine, namely the performance efficiency factor, has caused a decrease in the performance level of the machine, causing downtime